What laboratory testing can help differentiate a non‐envenomed from an envenomed snakebite?. Issue 3 (March 2016) - Miller, Barbara; Weakley, Jennifer; Sidhpura, Monali
Abstract : Evidence‐Based Answer : The international normalized ratio (INR), activated partial thromboplastin time (aPTT), and creatine kinase (CK) combined with a neurological examination will detect severe envenoming by 12 hours (SOR: B, prospective cohort in Australia). Normal laboratory coagulation testing at 6 hours excludes elapid envenoming in asymptomatic patients (SOR: B, case series in Australia). Bedside coagulation testing (the WBCT20) has low sensitivity (SOR: B, retrospective cohort in Sri Lanka). Limiting coagulation studies to only patients with severe clinical presentations will miss most crotalid bite coagulopathies (SOR: B, case series in the United States).